No antiarrhythmic effect of direct oral anticoagulants versus vitamin K antagonists in paroxysmal atrial fibrillation patients undergoing catheter ablation. (15th May 2021) - Zweiker, David; Manninger, Martin; Sieghartsleitner, Raphael; Ebner, Jakob; Pratl, Bernadette; Bisping, Egbert; Lercher, Peter; von Lewinski, Dirk; Riedlbauer, Rita; Rohrer, Ursula; Spronk, Henri M.H.; Zirlik, Andreas; et al.
Abstract: Introduction: Direct oral anticoagulants (DOACs) are superior to vitamin K antagonists (VKAs) for the prevention of stroke in atrial fibrillation (AF) patients with elevated stroke risk. Possible antiarrhythmic effects of DOACs have been discussed. We analyzed impact of DOAC treatment on recurrence-free survival after AF catheter ablation. Methods: Two-hundred and thirty-nine consecutive patients (median age 57 [IQR 48–64] years, 26.4% female) undergoing ablation for paroxysmal AF were included into this study. 68.6% of them received DOACs (DOAC group), 31.4% VKA (VKA group). The primary outcome was arrhythmia-free one-year survival. Results: DOAC patients had lower BMI, shorter history of AF, less arterial hypertension, less vascular disease, less use of antiarrhythmics and consequently lower CHA2 DS2 -VASc and HAS-BLED Scores. There was no difference in arrhythmia-free survival between DOAC and VKA groups (DOAC: 86.6%, VKA: 76.7%, p  = 0.286). Conclusions: Despite baseline characteristics favouring a better outcome of DOAC patients, arrhythmia-free survival was similar in both groups. Consequently, DOAC treatment did not have clinically relevant antiarrhythmic properties in these patients. Highlights: Direct oral anticoagulants have no antiarrhythmic effect in clinical practice. New oral anticoagulants do not prevent arrhythmia after pulmonary vein isolation. Factor Xa inhibitors do not influence outcome after atrial fibrillation ablation.